MODIFIKASI PERENCANAAN GEDUNG KONI PROVINSI KALIMANTAN TIMUR DENGAN MENGGUNAKAN METODE FLAT SLAB DENGAN DROP PANEL DAN SHEAR WALL - APRIYANI, RAHMA (KURVA S JURNAL MAHASISWA, 2018)
Currently the building are urgently needed in many major cities as spaces for residences , offices , place of businesses , and so forth . With the development of technology is also emerging innovations in the construction of tall buildings , especially in terms of the floor slab system . A flat slab reinforced concrete slab structures that do not use direct beam and using drop panels around the head of the column that serves as an additional buffer on the plate in bearing forces on the shear plate especially around the head of the column . In this final slab system to be discussed is the floor plate system using a flat slab with drop panels. The structure analysis step is divided into three stages, namely structural modeling, structural loading and structural analysis. The structure modeling stage is the process of entering structural planning data such as geometry, material and structural elements. At the loading stage of the structure, working loads are grouped into static and dynamic loads. Static load consists of dead load and live load while dynamic load is earthquake load which is analyzed by spectrum and time history response methods. The results of the structural analysis data are used as data in the modification of building structure element planning in accordance with the provisions of SNI 03-2847-2013. The results of the design obtained by slab thickness of 200 mm, 50 mm thick drop panel with a width of 240 cm either towards the x-axis and towards the y-axis, and with the use of a column with dimensions of 700 mm x 700 mm from 1st floor until 7th floor and column with dimensions of 500 mm x 500 mm for 8th floor. Shear wall is designed with a thickness of 400 mm